Determining system boundaries on commercial broiler chicken production system using ISO 14040/14044 guideline: a case study - Abdullah Sidek, 'Atiah; Suffian, S A; Al Hazza, Muataz Hazza Faizi; H. M., Yusof (Institute of Physics Publishing, 2018)
The demand of poultry product in Malaysia market shows an escalation throughout the year and expected to increase in the future. The expansion of poultry production has led to environmental concern in relation to their operational impact to environmentAt present, assessment of waste management of poultry production in Malaysia is lacking. A case study research was conducted in a commercial broiler farm to identify and assess the system boundaries in the lifecycle supply chain of broiler chicken production using ISO 14040/44 guidelines. ISO 14040/44 standard includes Life Cycle Assessment (LCA) framework guidelines to evaluate environmental influence associated with a product/process throughout its life span. All attributes associated with broiler operation is defined and the system boundaries is determined to identify possible inputs and outputs in the case study. This paper discuss the initial stage in the LCA process, which set the context of the research and prepare for the stage of Life Cycle Inventory.